The Geochemical Atlas of European ground water with emphasis on Hellas - Demetriades, A.; Reimann, C.; Birke, M. (Bulletin of the Geological Society of Greece, 2012)
A first impression of the geochemistry and quality of European ground water was obtained by using bottled mineral water as a sampling medium. In total, 1785 bottled waters were purchased from supermarkets of forty European countries, representing 1247 wells/drill holes/springs at 884 locations. All bottled waters were analysed for 72 parameters at the laboratories of the Federal Institute for Geosciences and Natural Resources (BGR) in Germany. The European geochemical maps give a first impression of the natural variation in ground water at the continental scale. The majority of European bottled waters are classified as of Ca-HCO3 type, because of the widespread carbonate lithologies, but there is considerable variation from Na-HCO3 type related to granitic rocks to Na-Cl type associated with deep saline brines. Since, the dominating lithology in Hellas comprises limestone, dolomitic limestone, marble, and maficultramafic rocks (ophiolites), the dominant major ions in Hellenic bottled waters are Ca2+, Mg2+, CO32- and HCO3-, and are, thus, classified in the Ca2+-Mg2+-HCO3- hydrochemical facies. The source aquifers of Hellenic bottled water are apparently continuously replenished by fresh water. Chromium, V and U are discussed, because of their importance in Hellenic ground water. In Europe, the former is clearly related to ophiolites, whereas V indicates the presence of recent volcanism and basaltic rocks, and U is associated with granitic intrusions and Bunter (central England) and Keuper (central Europe) sandstone of early and late Triassic, respectively. It can, therefore, be concluded that geology is one of the key factors influencing the observed element concentrations for a significant number of elements.